2023
DOI: 10.5812/jhrt-130772
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health Among Pregnant Women at Ilam, Iran: A KAP Study

Abstract: Background: Pregnancy is a unique period during a woman’s life and is characterized by complex physiological changes, which may adversely affect oral health. Objectives: The current study aimed at determining pregnant women’s knowledge, attitude and practice on oral health in 2018 to improve their knowledge, attitude and practice and subsequently decreasing oral diseases. Methods: In a cross- sectional study, 320 pregnant women referring to Ilam city health centers were selected through simple random sampling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
0
0
Order By: Relevance
“…Although the results of these studies vary, most of them have indicated that, globally including in Iran, pregnant women have little knowledge in this field. A study by Marc et al in Australia has found that pregnant women consider general health to be more important than oral health, with only 35% seeking dental care during pregnancy [12,14]. In a study by Adeniyi Abiola et al in Nigeria, most of the study's subjects had demonstrated a reasonable level of knowledge and a positive attitude towards oral health, which could be due to the high education level of the study participants; however, the knowledge and attitudes of pregnant women were not reflected in their oral hygiene practices [11].…”
Section: Introductionmentioning
confidence: 99%
“…Although the results of these studies vary, most of them have indicated that, globally including in Iran, pregnant women have little knowledge in this field. A study by Marc et al in Australia has found that pregnant women consider general health to be more important than oral health, with only 35% seeking dental care during pregnancy [12,14]. In a study by Adeniyi Abiola et al in Nigeria, most of the study's subjects had demonstrated a reasonable level of knowledge and a positive attitude towards oral health, which could be due to the high education level of the study participants; however, the knowledge and attitudes of pregnant women were not reflected in their oral hygiene practices [11].…”
Section: Introductionmentioning
confidence: 99%